2005
DOI: 10.1007/s11099-005-1011-0
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase in relation to higher plants

Abstract: The review incorporates recent information on carbonic anhydrase (CA, EC: 4.2.1.1) pertaining to types, homology, regulation, purification, in vitro stability, and biological functions with special reference to higher plants. CA, a ubiquitous enzyme in prokaryotes and higher organisms represented by four distinct families, is involved in diverse biological processes, including pH regulation, CO 2 transfer, ion exchange, respiration, and photosynthetic CO 2 fixation. CA from higher plants traces its origin with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(53 citation statements)
references
References 103 publications
1
51
0
1
Order By: Relevance
“…A phylogenetic tree of the carbonic anhydrase homologs identified in five grasses revealed that there were three major carbonic anhydrase subfamilies (CAα, CAβ and CAγ), consistent with previous data 14,45 (Fig. 2b).…”
Section: A R T I C L E Ssupporting
confidence: 90%
“…A phylogenetic tree of the carbonic anhydrase homologs identified in five grasses revealed that there were three major carbonic anhydrase subfamilies (CAα, CAβ and CAγ), consistent with previous data 14,45 (Fig. 2b).…”
Section: A R T I C L E Ssupporting
confidence: 90%
“…Excess salt concentration cause the closure of stomata, by decreasing the partial CO 2 pressure (Bethkey and Drew, 1992) as well as internal CO 2 concentration and consequently the activity of carbonic anhydrase (Table 1). There was an unexpected decline on CAA activity when 100 ppm (AsA) was applied none saline conditions because its activity is to large extent regulated by the CO 2 concentration (Tiwari et al, 2005). Therefore, the level of CAA in treated plants with (AsA) was lower than those which did not receive (AsA) treatment due to increased stomatal conductance as well as the internal CO 2 concentration in stress-free plants (Fariduddin et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study it was observed that water stress reduced SPAD chlorophyll value, photosynthetic attributes, NR, CA activities and leaf water potential ( Figures 1Á3, Table 1) and hence may ultimately lead to an overall decrease in crop yield. Decrease in photosynthetic rate mediated by water stress was the consequence of the closure of stomata, thereby decreasing CO 2 supply as well as internal CO 2 concentration (Tiwari et al 2005) and consequently a decrease in the activity of CA (Figure 3a), because its activity, to a large extent, is regulated by the CO 2 concentration (Tiwari et al 2005). Moreover water stress also inhibits the activity of Rubisco (Yardanov et al 2003) and that of other enzymes of photosynthesis (Lawlor 2002;Reddy et al 2005).…”
Section: Discussionmentioning
confidence: 99%